What Determines the Perception of Segmentation in Contemporary Music? - Phillips, Michelle; Stewart, Andrew J.; Wilcoxson, J. Matthew; Jones, Luke A.; Howard, Emily; Willcox, Pip; du Sautoy, Marcus; De Roure, David (Frontiers in Psychology, 2020)
Background: This study concerns perception of musical segmentation during live listening to contemporary classical music. It is not known how listeners segment music when typical section markers, such as cadences and fermatas, are absent (e.g. Sears, Caplin & McAdams). Contemporary music is often non-tonal and may not prioritize the musical phrase or notion of melody. Aims: The current study aimed to examine which musical features influence listeners’ decisions regarding section endings in a piece of contemporary music, Ligeti’s ‘Fanfares’. Methods: Data were gathered using a smartphone application (‘PRiSM Perception App’), designed for this study by the RNCM Centre for Practice & Research in Science & Music (PRiSM) and the Oxford e-Research Centre. 259 audience participants were asked to ‘tap’ when they felt that a section had ended. Subjective responses were captured, as well as contextual data about the participants. Results: Audience members demonstrated high levels of agreement regarding segmentation. Musical features which influenced decisions included changes in dynamic and changes in register in which motifs were played, and breaks in the musical texture (one piano hand resting). Self-report data analysis suggests that listeners were not always aware of how they made decisions regarding segmentation. Musical training may alter to what extent listeners rely on cues related to dynamic level, and a break in the musical texture. A listener’s sense of familiarity with contemporary repertoire does seem to influence perception of musical segments – participants who self-reported being familiar with contemporary music used a wider range of cues to make their decisions of segmentation (particularly cues related to change of register / pitch and a change in the musical material played by each piano hand). The factors which may influence judgement of musical segmentation are to some extent similar to those identified by music analysis (Steinitz, 2011) but in other ways different. Conclusions: Whether musically trained or not, and regardless of familiarity with contemporary classical music, listeners demonstrate commonalities in segmentation of musical information, which they are not always aware of. This study has implications for contemporary composers, performers, and audiences and how they engage with new music in particular.